Instilling Islamic Values ​​in Parenting a Father as a Single Parent: Penanaman Nilai-nilai Islam pada Pengasuhan Ayah sebagai Orang Tua Tunggal - Anggraini, Mardhiana; Putri, Yusmi Dwi; Raihana, Permata Ashfi; Yuwono, Susatyo (Universitas Muhammadiyah Sidoarjo, 2019)
The ideal family consists of father, mother and child, but it is different if there is spouse death or divorce so father or mother becomes single parent. Islam considers that mother is the main caregiver (madrasatul ula), but it is not found if there is death of a mother or child who follows their father when their parents divorce. Nevertheless, a single father is still optimize the nurturing to his children. This study aims to explore the internalization of Islamic values of a single father parenting. This study used qualitative methods with a phenomenological approach. The research subjects consisted of 6 single fathers. Data is collected with interview. Analysis is done by descriptive analysis. The results show that the values include religy, self value, responsible for the tasks, and social interaction. It can be concluded that a single father continues to carry out parenting by applying Islamic values.